Development of significant disease in a cohort of patients with non-specific enteritis on capsule endoscopy: clinical suspicion and a high base line Lewis score are predictive of Crohn's disease. - Mc Namara, Deirdre (My University, 2020)
Background: As with isolated ileitis the findings of nonspecific small bowel enteritis (NSE) on capsule endoscopy (CE) poses a clinical challenge. There is lack of available evidence to help clinicians to predict significant disease and long-term prognosis. Aim: To define the natural history of NSE in an Irish cohort. Methods: Patients with a finding of NSE were identified from a database. Subsequent investigations, treatments and diagnosis were recorded. Patients were grouped based on ultimate diagnosis: Crohn’s disease (CD), Irritable bowel syndrome (IBS), NSAIDs enteritis (NSAIDs), persistent NSE and no significant disease (NAD). Results: 88 patients, 46 (52%) male, mean age 52 ± 17.8 years were included with a mean follow up of 23 ± months. The ultimate diagnoses were NAD = 43 (49%), CD = 17 (19%), IBS = 14 (16%), NSAIDs = 12 (14%) and persistent NSE = 2 (2%). Significantly, more patients diagnosed with CD on follow up were referred with suspected CD. CD = 14/17 (82%) vs 13/57 (23%), p < 0.001. While a diagnosis of CD was associated with a positive baseline Lewis score (> 135); 11/17 (65%) CD versus 16/ 71 (23%). Female gender was associated with an ultimate diagnosis of IBS (OR 5, p < 0.02). Older age was associated with NSAIDs enteritis, while more subjects without significant gastrointestinal disease were anemic on presentation. Conclusion: The majority (49%) of NSE patients do not develop significant small bowel disease. CD occurred in 19% of NSE patients on follow up. Clinical suspicion and capsule severity are predictive of Crohn’s disease on initial CE.
PUBLISHED
Keywords: Capsule endoscopy; Crohn’s disease; Enteritis; Immunology, Inflammation & Infection; CROHN'S DISEASE; Capsule Endoscopy; Health